2021
DOI: 10.3389/fcvm.2021.619650
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors: Cardiotoxicity in Pre-clinical Models and Clinical Studies

Abstract: Since the approval of the first immune checkpoint inhibitor (ICI) 9 years ago, ICI-therapy have revolutionized cancer treatment. Lately, antibodies blocking the interaction of programmed cell death protein (PD-1) and ligand (PD-L1) are gaining momentum as a cancer treatment, with multiple agents and cancer types being recently approved for treatment by the US Food and Drug Administration (FDA). Unfortunately, immunotherapy often leads to a wide range of immune related adverse events (IRAEs), including several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 60 publications
(88 reference statements)
1
16
0
1
Order By: Relevance
“…A case described by Martinez-Calle et al showed that the patient did have IgG autoantibodies against cardiac troponin T, but it is unknown if the antibodies were present before initiation of ICI therapy [33]. Two other patients have shown autoantibody deposition in cardiac muscle, suggesting a direct relationship between the antibodies and myocarditis [34]. However, many more cases have stated that no autoantibodies were found on histology or blood tests [11,15,35], leading to the conclusion that autoantibodies are generally not involved in the pathogenesis of cardiotoxicity with ICIs.…”
Section: Generalmentioning
confidence: 99%
“…A case described by Martinez-Calle et al showed that the patient did have IgG autoantibodies against cardiac troponin T, but it is unknown if the antibodies were present before initiation of ICI therapy [33]. Two other patients have shown autoantibody deposition in cardiac muscle, suggesting a direct relationship between the antibodies and myocarditis [34]. However, many more cases have stated that no autoantibodies were found on histology or blood tests [11,15,35], leading to the conclusion that autoantibodies are generally not involved in the pathogenesis of cardiotoxicity with ICIs.…”
Section: Generalmentioning
confidence: 99%
“…Animal models have been used to study the effects of the ICI-associated immune reaction on the heart [14]. Genetic deletion of PD-1 in the BALB/c mouse line resulted in dilated cardiomyopathy (DCM) with accumulation of immunoglobulins on the cardiomyocytes' surface [15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a novel assay system, such as the co-culture of PSC-CMs and immune cells, may help us to gain a deeper understanding of the crosstalk between CMs and immune cells. Furthermore, efforts to develop such assay systems may help reveal the mechanisms underlying immune checkpoint inhibitor-related cardiotoxicity ( Michel et al, 2019 ; Behravesh et al, 2020 ; Xu et al, 2021 ) and to mimic such adverse effects in vitro . Another limitation of the 3D cardiac organoids/microtissues is that the degree of maturation for the fabricated organoids is not yet sufficient, when compared to adult cardiac tissues, in terms of morphology, function, and gene expression, and this prevents accurate predictions of drug-induced cardiotoxicity.…”
Section: Cardiac Organoids and The Prediction Of Cardiotoxicitymentioning
confidence: 99%